Evaluasi Hasil Edukasi Farmasis Pada Pasien Diabetes Melitus Tipe 2 Di Rumah Sakit Dr. Sardjito Yogyakarta - SESILIA ANDRIANI KEBAN; LUTFAN BUDI PURNOMO; MUSTOFA MUSTOFA (JURNAL ILMU KEFARMASIAN INDONESIA, 2013)
Diabetes mellitus (DM) is a metabolic disorder caused by a defect in insulin secretion or insulin action. Number of diabetic patients will increase if strategies are not prepared for preventing and controlling diabetes. This study aimed to evaluate the outcome of pharmacist education on the level of knowledge, level of medication adherence and diet, as well as the A1C value of type 2 diabetic patients in Dr. Sardjito Hospital Yogyakarta. This research was conducted prospectively using Nonrandomized Concurrent Control Trial. The number of subjects recruited were based on a three-months period and subjects were taken by consecutive sampling method. There were two groups: one group received education intervention for 3 months, and the other group as control did not receive education. Data were analyzed descriptively and quantitatively using Independent T and T-Paired test. The results showed that patients in the control group have developed an increase in the level of knowledge and adherence by themself, on the other hand patients in this group showed a decrease in A1C values, but the decrease was not as big as patients in the intervention group. Patient’s adherence to diet did not improve in either control nor intervention group. It can be concluded that education given by pharmacist can increase knowledge and adherence towards medication and decrease the A1C values of DM type-2 patients.